Analysis of Variations in Slogans Used in Advertisements for the Online Shopping Site Shopee: A Sociolinguistic Study - Putri Sarah; Nia Paramita; Nur Balia; Elpi Syahri Munanda; Faiza Zikrina; Yalfin Hafid; Ervan Defrizal (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study examines the variation of language in slogans used in advertisements on the online shopping site Shopee from a sociolinguistic perspective. With the increasing popularity of online shopping in Indonesia, Shopee utilizes various language strategies to attract and retain users. However, not all consumers understand the meaning and function of language variation in these advertising slogans. The purpose of this study is to identify the forms of language variation and explain their functions in the context of Shopee's promotions. The research method used is qualitative with a descriptive approach, analyzing 12 advertising slogans found on the Shopee shopping site. The results of the study indicate the presence of two types of language variation: foreign language terms, such as (cashback, flash sale, birthday sale, and big sale); and slang terms, such as (free shipping XTRA). In addition, two main language functions were identified. The first is the informational function to convey information about products or promotions, such as (guaranteed discounts, discounts of up to 50%, free shipping throughout Indonesia, and everything for 10.000 rupiah). The second is the directive function to encourage consumers to make purchases, such as (buy everything, come on, and now). This study provides insights into the language strategies used by Shopee to achieve effective communication in marketing products and attracting the attention of its target consumers.